Iron and copper complexes with antioxidant activity as inhibitors of the metastatic potential of glioma cells - Guerreiro, Joana F.; Gomes, Marco Antonio G. B.; Pagliari, Francesca; Jansen, Jeannette; Marafioti, Maria G.; Nisticò, Clelia; Hanley, Rachel; Costa, Rafael O.; Ferreira, Sarah S.; Mendes, Filipa; Fernandes, Christiane; Horn, Adolfo; et al. (RSC Advances, 2020)
Gliomas are the most common type of primary brain tumors, presenting high mortality and recurrence rates that highlight the need for the development of more efficient therapies. In that context, we investigated iron(iii) (FeL) and copper(ii) (CuL) complexes containing the tetradentate ligand 2-{[(3-chloro-2-hydroxy-propyl)-pyridin-2-ylmethyl-amino]-methyl}-phenol (L) as potential antimetastatic compounds in glioma cells. These complexes were designed to act as mimetics of antioxidant metalloenzymes (catalases and superoxide dismutase) and thus interfere with the production of reactive oxygen species (ROS), important signaling molecules that have been linked to the induction of Epithelial-Mesenchymal Transition (EMT) in cancer cells, a process associated with cancer invasion and aggressiveness. The results obtained have revealed that, in vitro, both compounds act as superoxide dismutase or catalase mimetics, and this translated in glioma cells into a decrease in ROS levels in FeL-treated cells. In addition, both complexes were found to inhibit the migration of monolayer-grown H4 cells and lead to decreased expression of EMT markers. More importantly, this behavior was recapitulated in 3D spheroids models, where CuL in particular was found to completely inhibit the invasion ability of glioma cells, with or without cellular irradiation with X-rays, which is suggestive of these compounds' potential to be used in combination with radiotherapy. Overall, the results herein obtained describe the novel use of these complexes as agents that are able to interfere with regulation of EMT and the invasive behavior of glioma cells, an application that deserves to be further explored.